DESIGN AND TEST OF A MULTI-DIMENSIONAL MICRO-VIBRATION SIMULATOR - WANG Bing; XU ZhenBang; YANG JianFeng; WANG XiaoMing; WU QingWen (Jixie qiangdu, 2018)
To simulate the micro-vibration of the space platform such as satellites,space stations and so on,a multidimensional micro-vibration simulator based on the Gough-Stewart configuration was designed.Firstly,the structural design of the multi-dimensional micro-vibration simulator was introduced.The theoretical model of the simulator is established by NewtonEuler’s method.In this model,the situation of misalignment between the origin of the relative reference frame and the barycenter of upper platform and load was considered.Combining with the principle of virtual work,the equations of the natural frequencies and mode shapes could be gained.Secondly,the modal of the simulator was analyzed by the finite element method and the analytical method.The first six natural frequencies and the modal shapes were obtained.The maximum error of FEA simulation is4.17% compared with the mathematical analytical solution.Finally,a prototype of the micro-vibration simulator was manufactured and its performance was testing.The test results indicate that the effective operating frequency of the simulator is up to 100 Hz,meeting the need of the vibration test.